2010
DOI: 10.1063/1.3265317
|View full text |Cite
|
Sign up to set email alerts
|

Generation of high currents of carbon ions with the use of subnanosecond near-infrared laser pulses

Abstract: Emission of carbon currents reaching values up to 2 A/cm(2) at a distance of 1 m from the laser ion source driven by the subnanosecond Prague Asterix Laser System operated at a fundamental wavelength of 1315 nm is reported. Graphite targets were exposed to intensities up to 5x10(16) W/cm(2) varying both the laser energy and the position of the laser beam focus with respect to the target surface. The maximum energy gain of carbon ions was approximately = 1 MeV/u. At high laser intensities the shape of time-of-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Such diamond detectors have been employed in time-of-flight (TOF) configuration to monitor the emission plasma obtained at PALS laboratory in Prague by using a laser pulse intensity of about 10 16 W/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such diamond detectors have been employed in time-of-flight (TOF) configuration to monitor the emission plasma obtained at PALS laboratory in Prague by using a laser pulse intensity of about 10 16 W/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the generation of ions with energy of few MeV/u and current densities of few A/cm 2 by the use of the subnanosecond, kJ-class laser at Prague Asterix Laser System (PALS) laboratory has been reported [1][2][3]. The beam parameters are estimated with application of various devices and techniques usually operated in "single shot" mode.…”
Section: Introductionmentioning
confidence: 99%
“…Placing the focus a few mm inside or in front of the target surface results in a larger irradiated area on surface, leading to higher ionization of carbon ions due to slower heat dissipation on a larger surface area during the plasma formation. 13 The dependence of ion yield on the position of the focal spot was discussed for MCI generation from Au, Pb, Ta, and C. 35,36 The larger laser spot area on target results in lower laser power density and, in general, lower ion charge state and energy. However, over a certain focal spot distance away from the target surface, the ion yield is increased due to the larger surface area ablated and the resulting larger volume of the laser plasma.…”
Section: Focal Point Dependencementioning
confidence: 99%
“…This is in agreement with previous results. 36 In Fig. 7, the EIA analyzer is set to allow ions with central energy-to-charge ratio of E/z = 5.3 keV which corresponds to the maximum of the ion energy distribution for the target biased at 9 kV.…”
Section: Focal Point Dependencementioning
confidence: 99%
“…The experiments recently performed at PALS facility in Prague have demonstrated that multi-MeV protons with current densities of ~A/cm 2 can be accelerated at modest laser intensities (~10 16 W/cm 2 ) by using a sub-nanosecondclass laser [5,6,7]. Nevertheless, the "standard" way of proton acceleration by using metallic targets, for instance, produces proton bunches which originate from the target surface contaminants (chemisorbed impurities containing hydrogen molecules).…”
Section: Introductionmentioning
confidence: 99%